Impact of Fermentation and Roasting on the Gut Health Protective Effects of Cocoa in High-Fat Diet Fed Mice - Weikart, Daphne (Curr Dev Nutr, 2020)
OBJECTIVES: Chronic inflammation is an important driver of co-morbidities of obesity. Studies have indicated that cocoa (Theobroma cacao) and cocoa polyphenols can exert anti-inflammatory and anti-obesity properties in animal models. Fermentation and roasting are important for flavor and aroma development of cocoa but have been reported to decrease total phenolic content (TPC).  The effect of these processing steps on anti-inflammatory bioactivity has not been examined in vivo. We examined the impact of fermentation and roasting on the anti-obesity and gastrointestinal protective effects of cocoa in high fat diet (HFD)-fed mice. METHODS: Male and female mice were fed HFD for 9 wks to induce obesity and then randomized to receive either HFD or HFD supplemented with one of seven cocoa powders (80 mg/g diet) for an additional 8 wks. The cocoa powders differed in terms of roasting (no roast or 30 min at 120°C or 170°C) and fermentation (no, cool, or hot). Body weights were measured weekly. Following euthanasia, serum and cecal digesta were collected. Visceral fat, liver, and spleen were collected and weighed. Small intestine and colon were collected and measured. Prior to euthanasia, gut permeability was measured in a subset of mice from each group. RESULTS: Mice treated with cocoa-supplemented diets had lower rate of weight gain: final body weights were 9–13% and 5–19% in males and females, respectively. Cocoa treatment also resulted in longer colon lengths (18–26% in males and 11–24% in females) and reduced gut permeability (50–75% lower) compared to HFD-fed controls indicating reduced colonic inflammation. While fermentation and roasting did impact chemistry and bioactivity, the unfermented, unroasted cocoa was not necessarily the most effective, and some combinations resulted in equivalent or improved bioactivity. Cytokine and microbial composition analysis are ongoing. CONCLUSIONS: Our results show that all treatments mitigated weight gain, colon inflammation, and gut permeability induced by HFD. The degree of fermentation and roasting and TPC may not predict efficacy. This indicates that it may be possible to develop processing steps to optimize both cocoa flavor and health-related bioactivity. FUNDING SOURCES: This work was funded by USDA AFRI.